Effect of segmental rim defect morphology on press-fit stability of the cementless acetabular cup: a finite element analysis - Zhang, Xin; Lin, Kewei; Feng, Bolin; Chen, Haicong; Zhong, Huan; Ouyang, Hanbin (Frontiers in Medicine, 2025)
IntroductionSegmental rim defect (SRD) of the acetabulum is a common type of osteolysis following primary total hip arthroplasty. Accurate quantitative evaluation of severity and morphology of the SRD can provide critical information to surgeons for decision-making on surgical reconstruction. Therefore, we aim to investigate the effect of morphologic features of SRDs on the press-fit stability of cementless cups.MethodsA 3D finite element model of Sawbones hemipelvic bone was developed using CT scan. Submodels with varying SRD geometries and locations were created, followed by Boolean reaming and virtual 1-mm press-fit implantation of a cementless cup. The press-fit stability was evaluated by using the push-out and lever-out tests based on quasi-static non-linear finite element analysis. The peak micromotion (PM) levels of all submodels at the bone-cup interface during the gait cycle were also compared.ResultsDespite the depth and width, the defect in the weight-bearing zone exhibited the lowest average push-out load of 2429 ± 294.19 N and lever-out moment of 100 ± 8.40 Nm comparing to those in other zones. The maximal push-out and lever-out loads of the cup decreased as either the width or depth of defect increased. The percentages of strength reduction for push-out and lever-out tests, respectively up to 47.8 and 34.1%, were significantly higher in the weight-bearing zone comparing to those in the other zones. During the gait cycle, all worst-scenario defects resulted in varying levels of increase in interfacial PM comparing to the intact acetabular rim. In the second half of the gait cycle, the defect in the weight-bearing zone produced the highest level of PM.ConclusionIn revision total hip arthroplasty (r-THA), a large SRD in the weight-bearing zone can result in the utmost loss of press-fit stability and a detrimental interfacial micromotion, which may lead to early loosening of the cup. Thus, an accurate quantitative evaluation of defect morphology is valuable for surgeons to develop a refined plan for reconstruction of initial stability of a cementless cup.